Is a corrupt government totally unacceptable?. Issue 4 (4th July 2017) - Cordero, Guillermo; Blais, André
Abstract: Corrupt governments are not always punished by voters. Under certain circumstances citizens consider voting for the incumbent party even if the party is perceived as corrupt. Using survey data for Spain, this article analyses what makes citizens reject (or not) the idea of voting for a corrupt party. Previous research has shown that party identification, ideology and political information play a role in voters' reactions to corruption. The article argues that voters judge corruption in relative terms; what matters is not how corrupt the incumbent party is perceived to be but whether it is deemed to be more corrupt than the other parties.